UJI EFEKTIFITAS GEL KROKOT MAGENTA (Portulaca oleracea) TERHADAP BAKTERI Propionibacterium acnes - Levi Puradewa; Tania Amelia (Program Studi Biologi - Universitas Katolik Widya Mandala Surabaya (kampus Kota Madiun), 2022)
Acne vulgaris (acne) is a skin disease that arises due to chronic inflammation with complex pathogenesis, which involves the sebaceous glands, follicular hyperkeratinization, excessive bacterial colonization, immune reactions, and inflammation. Magenta purslane (Portulaca oleracea) contains secondary metabolites of phenolic acid, and anthocyanins which have the main role as a plant colorant, this compound is a flavonoid derivative that can kill bacteria. The purpose of this study was to determine the effectiveness of the magenta purslane gel preparation against the bacteria Propionibacterium acne. The research method was carried out by planting Propionibacterium acnes bacteria and then tested with 3 treatments of clindamycin as a positive control, gel base as a negative control, and magenta purslane gel with a concentration of 10%. After 24 hours, the clear zone was measured using a caliper. The results of this study found that magenta purslane gel with a concentration of 10% could produce a clear zone of 9.46±0.68. This means that magenta purslane gel with a concentration of 10% has the potential to inhibit the growth of Propionibacterium acnes bacteria